Awareness and perception on greenwashing of selected Filipino consumers in Metro Manila - Recillo, Aeris Gabrielle R.; Oxales, Sarah Angelica (Quezon City College of Home Economics, University of the Philippines Diliman, 2023)
Consumers demand sustainability in clothing business practices due to the industry’s environmental impact, but some brands use deceptive marketing strategies, known as "greenwashing," to appear sustainable. This study analyzed the awareness and perception of selected Filipino consumers on the concept of greenwashing of fast fashion brands. A survey was distributed using purposive sampling to 100 respondents aged 18- 41 as of 2022 and are residing in Metro Manila who purchased from fast fashion brands, regardless of frequency. Then, ten willing survey respondents were interviewed. Descriptive analysis and thematic analysis were used to interpret the data gathered. The results of the study showed that consumers have a varying awareness of sustainability and greenwashing, and that their knowledge of sustainability did not necessarily translate into familiarity with greenwashing. Respondents are familiar with common greenwashing practices, such as claiming sustainability and recyclability but having only a small portion of the product made sustainably, not disclosing any information on materials and production or their recycling process, using of vague words like “natural” and “green”, and lacking transparency in sustainability reports. After learning about greenwashing and its common practices, consumers gained a negative perception on these. However, consumers still purchase from these brands due to other considerations, mainly affordability, comfortability, and aesthetic, along with other barriers such as the lack of information on brands and the sustainability of their practices. This reveals that there is an attitude-behavior gap among consumers and that even if they have a negative perception of a brand, there are still internal and external barriers that hinder them from prioritizing sustainable alternatives and doing more research about sustainable brands.
Thesis (Bachelor of Science in Clothing Technology) -- University of the Philippines Diliman
Bibliography: pages 79-80.
Keywords: Greenwashing -- Philippines -- Metro Manila; Clothing trade -- Sustainable methods -- Philippines -- Metro Manila; Fashion -- Philippines -- Metro Manila